Trend in the influenza vaccination success among children aged 6 months to 2 years in 4th Regional Health, Thailand - Oranat, Kawinpat; Tirapha, Sariyamon; Prutipinyo, Chardsumon; Kengganpanich, Mondha (Public Health Policy and Laws Journal, 2025)
This study is a cross-sectional analytical study. Its objective is to factors related with successful trend of influenza vaccination in children aged 6 months - 2 years in Region 4 Health. The study sample consists of 301 influenza vaccine providers working in community hospitals and sub-district health promotion hospitals in Nonthaburi Province, Ang Thong Province, and Phra Nakhon Si Ayutthaya Province. Data were collected using an online questionnaire that was quality-checked by experts. Data analysis involved descriptive statistics (frequency, percentage), chi-square tests, and Spearman's rank correlation coefficient. The research findings revealed that the overall level of availabilities of health systems was moderate (49.20%) to high (35.90%). The overall level of perception regarding influenza vaccine policy and barriers to service delivery was moderate (68.88%). The level of successful trend of influenza vaccination in children aged 6 months - 2 years in Region 4 Health was low (46.18%). factors related with the successful trend of influenza vaccination in children aged 6 months - 2 years in Region 4 Health include seven factors related to factor availabilities of health systems are 1) Leadership and governance, 2) Health Service System, 3) Health workforce, 4) Health information systems, 5) Access to Essential Medicines and Health Technology, and 6) Community health systems, which have a moderate correlation; and 7) Financing, which has a high correlation. The Policy factors and obstacles for influenza vaccine services has a low correlation. Statistical significance at level 0.05 (p-value <0.001) Results from this study Can use the information that has been developed to develop policies, guidelines, and improve the vaccine management system The system for providing vaccines in public health services is more effective. Which will increase the rate of influenza vaccination or other vaccines in children in the future Keywords: Success trends of Vaccination; Success of influenza vaccine services; Influenza vaccination services; Influenza vaccination in children aged 6 months 2 years